Potensi Klaster Industri Furniture dari Kayu di Wilayah Subosukawonosraten - Rina Wulandari; Retno Widodo Dwi Pramono; Widyasari Her Nugrahandika (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2018)
Industrial cluster concept has become a policy reference for regional economic development in various countries. Industrial clusters are defined as the geographic proximity of firms that are interconnected with each other with related institutions in a particular field, linked by commonalities and complementarities. Reflecting on the success of several developed and developing countries successfully developing industrial clusters, the Government of Indonesia sets an industry cluster approach to enhance competitiveness and accelerate economic development as set forth in Peta Panduan Pengembangan Klaster Industri Prioritas Tahun 2010-2014. Nevertheless, industrial cluster concept is a multidimensional and complex. In many discussions, industrial cluster concepts assessed without regard to the scientific components contained therein, leading to the failure of implementation this concept. Empirically, in Indonesia, the industry is dominated by SMEs naturally agglomerate, while theoretically, industrial agglomeration is an embryo of an industrial cluster. Therefore, researcher is interested to identify the potential clusters of the case of wooden furniture industry in Subosukawonosraten based on the spatial distribution of the industry. The method in this study using case study method which consist Average Nearest Neighbor analysis to identify industrial agglomeration and continued with descriptive qualitative analysis techniques. Industrial agglomeration through several phase to be ideal industrial cluster. There are four agglomeration of wooden furniture industry which potentially develop into cluster in Subosukawonosraten. Agglomeration of wooden furniture industry in Sragen, Boyolali, and Karanganyar is the most potential to develop into cluster compared to others. That is industrial agglomeration which is in phase closest to ideal industrial cluster seen based on agglomeration size, type of actor, collaboration between actors, and market area.